Survey on Sentiment-Topic Detection from Text (International Journal of Engineering and Computer Science, 2014)
Sentiment analysis or opinion mining aims to use automated tools to detect subjective information such as opinions, attitudes, and feelings expressed in text. An important part of our information-gathering behavior has always been to find out what other people think. With the growing availability and popularity of opinion-rich resources such as personal blogs and online review sites, new challenges and opportunities arise as people now can, and do, actively use information technologies to seek out and understand the opinions of others. This survey covers techniques and approaches that are used for sentiment analysis.